Um estudo exploratório sobre a aplicabilidade do método de controes internos do COSO para as empresas brasileiras de pequeno porte - D'Avila, Marcos Zahler (2005)
The Brazilian firms growth is the challenge to be considered within the microeconomic agenda in order to include the country in the global competition s context. For such growth to happen, it is necessary to overcome external barriers, such as taxation, financing, regulation and technological policies. Besides, internal barriers should also be overcome, such as organizational culture and management. This work discusses the management of such firms regarding its growth phase, from the use of the COSO Committee of Sponsoring Organizations internal control method. The purpose is to assess the applicability of such method over the brazilian small business, meanly at the moment in which the small firm become a medium sized company, considering that at this point a strict and on going oversight became impossible. Such applicability has been evaluated through analysis of writings describing the brazilian small business features in comparison with the COSO internal control method and also through inquiry to small business experts. The conclusions obtained indicates that the COSO internal control method is applicable for the brazilian small business if changes are carried out. Required changes includes a replacement of the focus on disclosure of financial statements to a new focus on management accounting, pointed out as a need by the experts, and also a higher degree of details and examples of practical cases, meanly about the identification of a set of usual risks for small business